Breast-Pren (Pain Relief) as a Natural Compress Innovation to Reduce Milk Damage in Breastfeeding Mothers - Dwi Gita Ariyani; Finda Tri Astuti; Lolia Apriyuni; Ratih Murni; Ririn Wulandari; Rosmawati Rosmawati; Viola Ade Triana (PT. Anagata Sembagi Education, 2024)
Based on research (Apriani, et al 2018), the most common breastfeeding problem is breast swelling due to breast milk dams that cause breast milk not to come out smoothly. Cold compresses are one solution to the problem. Indonesia is a region rich in natural resources. These natural resources are not only used for food, but can also be an alternative medicine. Red betel is a plant that has a pain-reducing effect. The content of cabbage leaves helps in increasing blood perfusion to the swelling area, dilates capillaries and acts as a counter barrier so as to reduce swelling and inflammation of the breast so that milk flows Based on the description above, the author makes a product innovation, namely